Learner-led flipped classroom and undergraduate academic achievement: a new approach - Preece, Abdul Shakour Duncan; Hamed, Popoola Kareem (2018)
Flipped Classroom Method (FCM), a sub-category of blended learning, is a renowned teaching method that combines online learning with face to face instruction. Yet, the onus of preparing the online resources and classroom activities falls upon the teacher, meaning that it can still be considered to be rather teacher-centered in nature. The authors set about adapting FCM to make it truly learner-centered by giving students the opportunity to lead the flipped classroom, in consultation with their lecturer. This novel approach was termed 'Learner-led Flipped Classroom' (LLFC). The researchers conducted a quasi-experiment at a faculty of education in a Malaysian university to determine the effects of LLFC on learners' academic achievement. The intervention lasted five weeks using a course entitled 'Curriculum and Instruction'. The experimental group (45) were exposed to LLFC while the control group (33) experienced conventional teaching. The results of the pre-test and post-test indicated that LLFC had a statistically significant impact on the academic achievement of the experimental group compared to the control group. Hence, LLFC shows potential as a learner-centred adaptation of FCM that can enhance undergraduate students’ academic achievement.